Self-perceived performance and satisfaction with performance of daily activities in persons with multiple sclerosis following interdisciplinary rehabilitation. (March 2014) - Lexell, Eva Månsson; Flansbjer, Ulla-Britt; Lexell, Jan
Abstract Purpose: To assess self-perceived performance and satisfaction with performance of daily activities in persons with multiple sclerosis (MS) on admission to and at discharge from interdisciplinary rehabilitation. Method: A retrospective study with a pre-post design. Twenty-seven women and 16 men with MS (mean age 51 years; median EDSS 6.5) participated in an individualised, goal-oriented, interdisciplinary, rehabilitation programme (average length 4 weeks). The Canadian Occupational Performance Measure (COPM) was used on admission to rehabilitation and at discharge. Results: On admission, the persons prioritised 216 activities that they perceived difficult to perform (mean number 3, range 2–8). Of these, 136 (63%) were in the COPM area of self-care, 52 (24%) in productivity and 28 (13%) in leisure. The lowest mean ratings of performance were found in the subgroups active recreation, community management and socialisation, and for satisfaction in the subgroup socialisation. For about 60% of the 216 prioritised activities, ratings of COPM performance as well as satisfaction were higher at discharge than on admission. For 18 (42%) and 24 (56%) persons, respectively, the mean change scores of performance and of satisfaction were equal to or greater than 2.0 at discharge, indicating a clinically significant change. Conclusions: Persons with MS can experience problems with all types of daily activities upon admission to rehabilitation, but also perceive improvements in their performance and satisfaction with performance in these activities at discharge from rehabilitation. Using patient-reported outcome measures, such as the COPM, may contribute to a broader understanding of the benefits of interdisciplinary rehabilitation in persons with MS. Implications for Rehabilitation Persons with MS can perceive problems with all types of daily activities which have to be considered during interdisciplinary rehabilitation. Following interdisciplinary rehabilitation, persons with MS can perceive improvements in their performance and satisfaction with performance in all types of daily activities. Patient-reported outcome measures can contribute to a broader understanding of the benefits of interdisciplinary rehabilitation in persons with MS.